Menguasai Bahasa Inggris dalam Satu Menit: Pengembangan Bahasa Inggris di STAIBA Kediri - Hesty Puspita Sari; Binti Su’aidah Hanur; Nurma Atalsa Sofansyah Suwarni (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
Due to the fact that students will eventually enter the workforce, English proficiency plays a crucial role in their education. The world of work requires workers who have the ability to speak English orally and in writing. Students of the PIAUD study program in the pesantren environment who carry out their daily routines in the pesantren environment must be ready to enter the world outside the pesantren with a variety of chosen jobs. With the routine of Islamic boarding school activities which are very minimal in the opportunity to learn English, students who graduate from boarding schools feel that they are lacking in mastering the international language. In addition, the lack of motivation also greatly affects them in learning English. Based on the problems faced by students in Islamic boarding schools, it is necessary to provide motivation and learn English that is able to change their mindset in learning English easily and quickly. The development of English in the "Mastering English in One Minutes" activity by presenting natives from Canada together with English language study students was carried out face to face after previously students received online classes 3 times in meetings. This development uses the question and answer method, where PIAUD study program students can directly ask and practice English natively and will provide a golden opportunity to study briefly and increase their motivation in learning English. So it is necessary to organize Community Service activities to improve students' English mastery in the Islamic boarding school environment